Influence of slat attack angle and pitch ratio on turbulent hydrothermal characteristics in a louvered two-pass square channel. (November 2019) - Liou, Tong-Miin; Wang, Chun-Sheng; Tseng, Jui-Cheng; Hsieh, I-Ming; Chen, Chieh-Chu
Highlights: An innovative design of 3-D louver-type turbulator is proposed. Detailed PIV and IRT measurements of flow and temperature fields are conducted. The effects of slat attack angle and pitch ratio on Nu, f, and TPF are revealed. A compilation of Nu - f data for both previous and present designs is presented. Abstract: This study reports an innovative design of 3-D louver-type turbulator based on previous ribs, baffles, and 2-D louver-type turbulators. Its effects on turbulent flow field, detailed temperature distribution, and pressure loss in a two-pass channel with square cross-section are investigated by Particle Image Velocimetry (PIV), Infrared Thermography (IRT), and pressure transducer. Four pitch ratios ( Pi / DH ), namely 1, 2, 3, and ∞, are explored, and the slat attack angle ( α ) of the louver-type turbulator ranges from −40° to 30°. The Reynolds number ( Re ) for PIV and IRT measurement is fixed at 10, 000 and in the range of 5000–20, 000, respectively. It is found that the present turbulators with Pi / DH = ∞ not only disturb the core flow and degenerate wake zone behind the turbulator but also induce four pairs of Dean-like counter-rotating vortices which result in strong impingement on the bottom and top walls. The main contributions of this study are twofold: (1) the present design fills the blank at moderate friction factor ratio ( f ‾ / f ∞ ≤100) compared with previous ribs and baffles; (2) it attains much higher Nusselt number ratio ( Nu ‾ / Nu ∞ up to 4.4) at that f ‾ / f ∞ region or for the same value of Nu ‾ / Nu ∞ the value of f ‾ / f ∞ is 44.1% lower.